An anomalous origin of the middle meningeal artery - Royle, Gavin (1973)
A human skull is described in which the middle meningeal artery probably arose bilaterally from the lacrimal artery. The branches of the middle meningeal vessels, however, were normal both in their position and distribution. This anomaly is a rare occurrence and is of neurosurgical importance.